Breaking the Chain of Dependence: Community Empowerment and Decentralized Solutions for Education in Remote Indonesian Villages - Hamsah, Hamsah; Rahman, Rahmania; Risal, Risal (DISCOURSE: Indonesian Journal of Social Studies and Education, 2025)
This research analyzes the phenomenon of lack of access to education in Beringin Village, Ranoyapo Sub-district, South Minahasa Regency, through the perspective of Dependency Theory. It focuses on explaining how dependence on external parties, such as the central and local governments, creates structural inequalities that hinder educational development in remote areas. The focus of this research is SD Negeri Beringin, the only primary school in the village, which has very limited educational facilities. Field observations show that the school lacks adequate classrooms, textbooks and teaching staff. In addition, poor infrastructure, such as hard-to-reach roads, exacerbates the accessibility problem. Through a qualitative method with data collection through observation, in-depth interviews with teachers, parents and community leaders, as well as a study of policy documents, this study found that dependence on external policies, lack of resource allocation and lack of local initiatives are the main factors of this problem. The results of this study are expected to inform the government and other stakeholders in formulating more inclusive and equitable education policies.